Efficacy and safety of multifocal intraocular lenses following cataract and refractive lens exchange: Metaanalysis of peer‐reviewed publications. Issue 2 (February 2016) - Rosen, Emanuel; Alió, Jorge L.; Dick, Burkhard H.; Dell, Steven; Slade, Stephen
Abstract : N/A: We performed a metaanlysis of peer‐reviewed studies involving implantation of a multifocal intraocular lens (IOL) in presbyopic patients with cataract or having refractive lens exchange (RLE). Previous reviews have considered the use of multifocal IOLs after cataract surgery but not after RLE, whereas greater insight might be gained from examining the full range of studies. Selected studies were examined to collate outcomes with monocular and binocular uncorrected distance, intermediate, and near visual acuity; spectacle independence; contrast sensitivity; visual symptoms; adverse events; and patient satisfaction. In 8797 eyes, the mean postoperative monocular uncorrected distance visual acuity (UDVA) was 0.05 logMAR ± 0.006 (SD) (Snellen equivalent 20/20 −3 ). In 6334 patients, the mean binocular UDVA was 0.04 ± 0.00 logMAR (Snellen equivalent 20/20 −2 ), with a mean spectacle independence of 80.1%. Monocular mean UDVA did not differ significantly between those who had a cataract procedure and those who had an RLE procedure. Neural adaptation to multifocality may vary among patients. Financial Disclosure : Dr. Alió is a clinical research investigator for Hanita Lenses, Carl Zeiss Meditec AG, Topcon Medical Systems, Inc., Oculentis GmbH, and Akkolens International BV. Dr. Dell is a consultant to Bausch & Lomb and Abbott Medical Optics, Inc. Dr. Slade is a consultant to Alcon Surgical, Inc., Carl Zeiss Meditec AG, and Bausch & Lomb. None of the authors has a financial or proprietary interest in any material or method mentioned.